Negotiating Visibility and Invisibility among Romani families in Bogota, Colombia - Acuña Cabanzo, Esteban (Romano džaniben, 2021)
The article explores how visibility and invisibility have shaped the lives of Romani (Rrom) people in Bogota, Colombia. Through an ethnographic perspective, it presents vignettes of daily life and extraordinary events that are part of Romani experiences in the city and resulted from twelve years of accumulated fieldwork experiences. It relies on these descriptions to problematize simplistic understandings of the visible/invisible conceptual pairing, weaving them instead as negotiated strategies tied to quotidian interactions, specific historical moments and local contexts. The text proposes a timeline of three distinct episodes in the relations of Roma with non-Roma (gadye), including (i) a period of "passing" strategies; (ii) a period of mediated visibility as negotiations with the Colombian state took place; and a (iii) contemporary moment where families have begun to understand the limitations of an ethnic recognition process.